Organizational interventions: facing the limits of the natural science paradigm - Griffiths, A. (Scandinavian Journal of Work, Environment & Health, 1999)
This paper reviews current challenges in the conceptualization, design, and evaluation of organizational interventions to improve occupational health. It argues that attempts to confirm cause-and-effect relationships and allow prediction (maximize internal validity) are often made at the expense of generalizability (external validity). The current, dominant experimental paradigm in the occupational health research establishment, with its emphasis on identifying causal connections, focuses attention on outcome at the expense of process. Interventions should be examined in terms of (i) conceptualization, design and implementation (macroprocesses) and (ii) the theoretical mediating mechanisms involved (microprocesses). These processes are likely to be more generalizable than outcomes. Their examination may require the use of both qualitative and quantitative methodologies. It is suggested that such an approach holds unexplored promise for the healthier design, management, and organization of future work.
Keywords: evaluation; occupartional health; philosophy of science; qualitative research; quantitative research; work design